Foreword - Tapiwa Chagonda (The Thinker)
As the African continent stands at the cusp of profound technological advancement, it finds itself compelled to confront both the pros and the cons of the digital revolution. Artificial intelligence (AI), robotics, mobile commerce, and advanced machine learning (ML) are no longer emerging phenomena in distant economies; they are deeply embedded in Africa’s sociopolitical, economic, and cultural fabric. This special issue of Technology and Society within the African Context, illuminates the multidimensional implications of these advancements, recognising the urgency of both proactive engagement and ethical stewardship. Through ten insightful contributions, this issue seeks to provide a deep understanding of how Africa might harness these technologies to foster resilience, inclusivity, and sustainability across sectors.